IMPROVEMENT OF FRESHWATER RESOURCES MANAGEMENT MODELS ON AN INNOVATIVE BASIS IN THE CONDITIONS OF SUSTAINABLE DEVELOPMENT - SERBOV, Nikolay (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Effective use of freshwater resources is an extremely urgent problem in the regions of the Black Sea region due to their uneven distribution on the territory, high level of strategic needs and complex ecological situation. The realization of the above priorities requires, first of all, political will, organizational and economic reforms in the industry, as well as the establishment of a close dialogue between representatives of the state, regional governing bodies, the public and business environment, and science. That is why the improvement of freshwater resource management models on an innovative basis in conditions of sustainable development is quite urgent. The purpose of the article is the process of improving freshwater resource management models on an innovative basis in conditions of sustainable development. The regularities of the water supply of the Odesa region in the context of freshwater resource management are studied. The research is structured on the basis of water management zoning, carried out in accordance with the existing river basins (Northern, Central, Primisky (Pridnistrian), South-Western, Danube water management regions). The peculiarities of economic activity and its impact on the state of freshwater resources within the selected districts are taken into account. It was determined that the Odesa region is characterized by uneven distribution of surface water reserves. The need to determine the investment support reserves of the system of regional management of fresh water resources has been proven. An assessment of the forecast value of capital investments for environmental protection in the Odesa region for 2022, which is 73.2 million UAH, and an estimate of the forecast value for 2022 for current costs for environmental protection in the region, which is 627.0 million UAH. A model of sustainable socio-humanitarian and ecologically balanced management of freshwater resources at the regional level has been developed, which takes into account innovative forms of interaction in the field of water use (corporatization, clustering, concession, capitalization, creation of holdings and associations) and the important role of public-private partnerships. The proposed model requires the transformation of the target orientations of the functioning of the water management complex in the direction of meeting the needs of current and future generations in freshwater resources, ensuring a safe environment and protection from the natural possibilities of water, which should contribute to the necessary institutional and structural transformations at the level of regions, districts and communities. The orientations of the strategic development of the system of regional management of freshwater resources have been defined: actualization of public activity, provision of productive and balanced use of natural and economic resources, including human capital, on the basis of diversification of innovative forms of relationships in the management system itself in the context of institutional transformations.